2002
DOI: 10.2320/matertrans.43.856
|View full text |Cite
|
Sign up to set email alerts
|

New Aspects of Structural and Magnetic Behaviour of Martensites in Ni-Mn-Ga Alloys

Abstract: The structural changes and magnetic anomalies accompanying martensitic transformations in Ni-Mn-Ga alloys are briefly discussed. The role of lattice tetragonality of martensite in the reduction of magnetic field needed for the observation of large magnetostrain effect is theoretically analyzed, considering the compensation of the magnetic anisotropy. The possibility of the field reduction is based on the previously observed lattice parameter dependence on the temperature and proper fit of the alloy specimen sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 18 publications
(41 reference statements)
2
14
0
Order By: Relevance
“…2), in the mixed martensite/austenite region. Chernenko et al [31] reported that a strain of >1% can be induced in the mixed region by a relatively weak magnetic field in specimens with DT M = M s À M f 6 10 K. The lower activation field needed for the high temperature actuation is consistent with previous observations [22].…”
Section: Room-and High-temperature Magneto-mechanical Propertiessupporting
confidence: 81%
“…2), in the mixed martensite/austenite region. Chernenko et al [31] reported that a strain of >1% can be induced in the mixed region by a relatively weak magnetic field in specimens with DT M = M s À M f 6 10 K. The lower activation field needed for the high temperature actuation is consistent with previous observations [22].…”
Section: Room-and High-temperature Magneto-mechanical Propertiessupporting
confidence: 81%
“…It can be helpful to characterize different Heusler compounds by their average concentration of valence electrons, which is defined as an electron-to-atom ratio [13,16,17]. The parameter e/a is a measure of the electronic filling and allows in a rough way to distinguish in the phase diagram of the ternary alloys the range of stability for the martensitically unstable alloys.…”
Section: Heusler Alloys Selected For This Studymentioning
confidence: 99%
“…In examining the magnetic properties of Ni 2+x+y Mn 1−x Ga 1−y alloys, the approach based on using the total electron concentration e/a has certain limitations, since the magnetic moment in these alloys [89], and (b) concentration dependence of tetragonal distortion of the crystal structure in Ni2+x+yMn1−xGa1−y alloys [97].…”
Section: A Ferromagnetic Transitionmentioning
confidence: 99%
“…The data in Refs [56,97,98] suggest that the ratio c/a, which gives the tetragonal distortion of the cubic lattice caused by the transition to the martensitic state, depends on alloy composition. As Figure 9b shows, c/a ≈ 0.94 for alloys in which the electron concentration e/a ∼ 7.4−7.6.…”
Section: Structural Distortionsmentioning
confidence: 99%